1986
DOI: 10.1084/jem.164.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiple organ-localized autoimmune diseases in nude mice after reconstitution of T cell function by rat fetal thymus graft.

Abstract: The T cell function of congenitally athymic nude mice and rats, as well as the severe immunodeficiency resulting from thymic dysplasia in humans, can be corrected by implantation of intact thymus or thymic epithelium (1-5). Either syngeneic or allogeneic thymic grafts are effective for reconstituting T cell functions in congenitally thymus-deficient rodents (6-10), although these functions are generally less effective than those of intact normal animals. Such reconstituted nude mice (grafted with allogeneic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…The previous study (1) showed the development ofmultiple organ-localized autoimmune disease in TG nude mice. To characterize the effector cells in these autoimmune diseases, passive transfer of the lesions was attempted .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study (1) showed the development ofmultiple organ-localized autoimmune disease in TG nude mice. To characterize the effector cells in these autoimmune diseases, passive transfer of the lesions was attempted .…”
Section: Resultsmentioning
confidence: 99%
“…Female BALB/c nu/nu mice, 5 wk of age, (CleaJapan Inc.) were grafted under each kidney subcapsule with two lobes ofthymic rudiments . These TG nude mice developed multiple organ-localized autoimmune diseases as reported previously (1). Incidence of the diseases assessed by histological examination in 109 TG nude mice, which were used as donors for the transfer experiments, was as follows : ovary, 92%; thyroid gland, 72 %; stomach, 72% ; adrenal gland, 44% ; salivary gland, 98%.…”
Section: Brief Definitive Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The destruction of allogeneic NNR grafts in this circumstance, compared with similar syngeneic NNR grafts, indicates that NNR as a tissue is only partially immune-privileged. As mentioned previously, allogeneic grafts of testis (16,20), neonatal retinal pigment epithelium (10), and epithelium-deprived corneas (14) survive almost indefinitely beneath the kidney capsule, which is characteristic of tissues that express complete immune privilege. In the case of testis, neonatal retinal pigment epithelium, and epithelium-deprived cornea grafts, constitutive expression of CD95 ligand (CD95L) has been implicated in conferring on these tissues the immune-privileged status (10,14,16).…”
Section: Discussionmentioning
confidence: 99%